TINJAUAN BENTUK DAN MAKNA TAUR-TAUR SIBUAT GULOM DI DESA HINALANG KECAMATAN PURBA KABUPATEN SIMALUNGUN - Rosenta Girsang (Universitas Negeri Medan, 2013)
This paper discusses the shape and meaning of the song Taur - Taur Sibuat Gulom . This research was carried out due to lack of society Simalungun especially young people who know , know and be able to sing Taur - Taur Sibuat Gulom because of the times . This paper reveals that the shape of the song Taur - Taur Sibuat Gulom consists of three forms or themes are as follows A theme found in bars 1 - 52 bars , theme bars B are at 53 - 79 bars first beat , and the theme of C contained in bar 79 - 97 beats a second time signatures . The meaning of the song Taur - Taur Sibuat Gulom presented typically contains romance young people who meet in a shower or bathing place that begins meeting , introductions , relationships . Each folk song , in principle, has a characteristic that distinguishes the folk songs which come from other ethnic . The song is many uses legato where it is a singing technique called Inggou Simalungun . This song lyric but give priority to the development of the melody used is repetition.